2019
DOI: 10.3390/met9080872
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Corrosion Resistance of SA106B Low-Carbon Steel Fabricated by Rotationally Accelerated Shot Peening

Abstract: The corrosion resistance of a SA106B carbon steel with a gradient nanostructure fabricated by rotationally accelerated shot peening (RASP) for 5, 10, 15 and 20 min was investigated. Electrochemical tests were carried out in the 0.05 M H 2 SO 4 + 0.05 M Na 2 SO 4 and 0.2 M NaCl + 0.05 M Na 2 SO 4 solutions. The experimental results showed that the sample RASP-processed for 5 min exhibited the best corrosion resistance among them. TEM analysis confirmed that the cementite dissolution and formation of nanograins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Figures 1(a) to (d) depict the representative normalized microstructures. It can be seen that the samples have ferritic-pearlitic microstructures, which is consistent with the microstructure of similar steels [11][12][13][14][15][16]. By increasing the holding time at the austenitization temperature, the microstructures became coarser.…”
Section: Resultssupporting
confidence: 80%
“…Figures 1(a) to (d) depict the representative normalized microstructures. It can be seen that the samples have ferritic-pearlitic microstructures, which is consistent with the microstructure of similar steels [11][12][13][14][15][16]. By increasing the holding time at the austenitization temperature, the microstructures became coarser.…”
Section: Resultssupporting
confidence: 80%
“…CPE (Q) was commonly used to represent the capacitances of oxide layer to account for the deviation from the ideal capacitive behavior due to surface inhomogeneity, roughness and adsorption effects. 19,20 Based on the results of electrochemical impedance spectroscopy, a positive trend in the anticorrosive nature of oxide lms were indicated by simultaneous injection of zinc and aluminum into high temperature primary circuit water.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Moreover, the shot peening process can significantly change the surface integrity of the target material, and thus promise to improve the mechanical properties and fatigue strength of critical parts [18]. Lei et al [19] reported that the shot peening process induced cementite dissolution and the formation of nanoparticles, contributing positive effects on the corrosion behavior of the SA106B low-carbon steel. The interesting work of Kumar et al [20] proposed that Ti-13Nb-13Zr alloy after the ultrasonic shot peening process showed a lower corrosion rate.…”
Section: Introductionmentioning
confidence: 99%